Influence of Nutrition Education with Calendar Method in Diabetic Patients' Blood Glucose - Setyoadi Setyoadi; Heri Kristianto; Siti Nur Afifah (NurseLine Journal, 2018)
Diabetes mellitus is a disease that required good self-management. Noncompliance in diet and meal plans cause the instability of blood glucose levels. Nutrition education calendar method can improve knowledge and ability to consume food that matches the number, hours and types with dietary adjustments listed in the calendar diet. This study aimed to determine the effect of nutrition education calendar method on blood glucose levels of patients with type 2 diabetes mellitus in Community Health Center Pakis Malang. Pre-experimental design one group pretest-posttest with purposive sampling was conducted in this study and sample obtained as many as 21 people. Blood glucose levels were measured before and after the nutrition education calendar methods. Compliance in using calendar method with the observation sheet. Statistical analysis values obtained by Wilcoxon, the p-value of 0.007 (p <0.05). The results of the analysis, 16 respondents showed a decrease in blood glucose levels and 5 respondents experienced an increase in blood glucose levels after the given intervention. It can be concluded that there are differences between blood glucose levels before and after nutrition education calendar method. Differences in blood glucose levels can be influenced by controlling diet respondent in accordance with the calendar method in education, but also antidiabetic drugs, and sports. Should be added to the control group to determine objectively the effect of nutrition education on the calendar method.